Enhancing the field emission properties of Se-doped GaN nanowires. (20th May 2016) - Li, Enling; Wu, Guishuang; Cui, Zhen; Ma, Deming; Shi, Wei; Wang, Xiaolin
Abstract: Pure and Se-doped GaN nanowires (NWs) are synthesized on Pt-coated Si(111) substrates via chemical vapor deposition. The GaN NWs exhibit a uniform density with an average diameter of 20–120 nm. The structure of the NWs is wurtzite hexagonal, and the growth direction is along [0001]. Field emission measurements show that the Se-doped GaN NWs possess a low turn-on field (2.9 V μ m −1 ) compared with the pure GaN NWs (7.0 V μ m −1 ). In addition, density functional theory calculations indicate that the donor states near the Fermi level are mainly formed through the hybridization between Se 4p and N 2p orbitals and that the Fermi level move towards the vacuum level. Consequently, the work functions of Se-doped GaN NWs are lower than those of pure GaN NWs.